Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which conditional completes the Law of Syllogism, let's first understand what the Law of Syllogism is:
The Law of Syllogism states that if we have two conditionals: [tex]\( p \rightarrow q \)[/tex] and [tex]\( q \rightarrow r \)[/tex], then we can infer a third conditional: [tex]\( p \rightarrow r \)[/tex].
Given:
- [tex]\( p \rightarrow q \)[/tex] (Read as: If [tex]\( p \)[/tex] then [tex]\( q \)[/tex])
We are supposed to identify the correct choice that should be in the form of [tex]\( q \rightarrow r \)[/tex] so that we can deduce [tex]\( p \rightarrow r \)[/tex].
Let's analyze each choice:
1. [tex]\( q \rightarrow 1 \)[/tex]
- This statement means if [tex]\( q \)[/tex] then [tex]\( 1 \)[/tex]. However, [tex]\( 1 \)[/tex] is not in our original statements [tex]\( p, q, r \)[/tex]. This does not help infer [tex]\( p \rightarrow r \)[/tex].
2. [tex]\( q \rightarrow p \)[/tex]
- This means if [tex]\( q \)[/tex] then [tex]\( p \)[/tex]. It does not match the required form [tex]\( q \rightarrow r \)[/tex] and does not help us infer [tex]\( p \rightarrow r \)[/tex].
3. [tex]\( r \rightarrow q \)[/tex]
- This means if [tex]\( r \)[/tex] then [tex]\( q \)[/tex]. This is actually the reverse of what we need. However, thinking of contrapositive logic, it is equivalent to saying [tex]\( \neg q \rightarrow \neg r \)[/tex] which is still not in our required form [tex]\( q \rightarrow r \)[/tex].
4. [tex]\( p \rightarrow 1 \)[/tex]
- This means if [tex]\( p \)[/tex] then [tex]\( 1 \)[/tex]. Similar to choice 1, [tex]\( 1 \)[/tex] is not in our original statements [tex]\( p, q, r \)[/tex]. Hence, this does not help infer [tex]\( p \rightarrow r \)[/tex].
Among these conditionals, analyzing [tex]\( r \rightarrow q \)[/tex] (choice 3), let's think step-by-step:
If we have:
- [tex]\( p \rightarrow q \)[/tex] (given)
- [tex]\( r \rightarrow q \)[/tex] (choice 3)
Using contrapositive of [tex]\( r \rightarrow q \)[/tex]:
- [tex]\( \neg q \rightarrow \neg r \)[/tex]
From original [tex]\( p \rightarrow q \)[/tex]:
- Contrapositive of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \neg q \rightarrow \neg p \)[/tex]
If [tex]\( \neg q \rightarrow \neg p \)[/tex] holds true and we assert [tex]\( \neg q \rightarrow \neg r \)[/tex] holds, logically, we can deduce [tex]\( p \rightarrow r \)[/tex].
Therefore, conditional [tex]\( r \rightarrow q \)[/tex] is logically equivalent to helping in constructing [tex]\( p \rightarrow r \)[/tex].
Thus, the correct choice is [tex]\( \boxed{3} \)[/tex]: r \rightarrow q
The Law of Syllogism states that if we have two conditionals: [tex]\( p \rightarrow q \)[/tex] and [tex]\( q \rightarrow r \)[/tex], then we can infer a third conditional: [tex]\( p \rightarrow r \)[/tex].
Given:
- [tex]\( p \rightarrow q \)[/tex] (Read as: If [tex]\( p \)[/tex] then [tex]\( q \)[/tex])
We are supposed to identify the correct choice that should be in the form of [tex]\( q \rightarrow r \)[/tex] so that we can deduce [tex]\( p \rightarrow r \)[/tex].
Let's analyze each choice:
1. [tex]\( q \rightarrow 1 \)[/tex]
- This statement means if [tex]\( q \)[/tex] then [tex]\( 1 \)[/tex]. However, [tex]\( 1 \)[/tex] is not in our original statements [tex]\( p, q, r \)[/tex]. This does not help infer [tex]\( p \rightarrow r \)[/tex].
2. [tex]\( q \rightarrow p \)[/tex]
- This means if [tex]\( q \)[/tex] then [tex]\( p \)[/tex]. It does not match the required form [tex]\( q \rightarrow r \)[/tex] and does not help us infer [tex]\( p \rightarrow r \)[/tex].
3. [tex]\( r \rightarrow q \)[/tex]
- This means if [tex]\( r \)[/tex] then [tex]\( q \)[/tex]. This is actually the reverse of what we need. However, thinking of contrapositive logic, it is equivalent to saying [tex]\( \neg q \rightarrow \neg r \)[/tex] which is still not in our required form [tex]\( q \rightarrow r \)[/tex].
4. [tex]\( p \rightarrow 1 \)[/tex]
- This means if [tex]\( p \)[/tex] then [tex]\( 1 \)[/tex]. Similar to choice 1, [tex]\( 1 \)[/tex] is not in our original statements [tex]\( p, q, r \)[/tex]. Hence, this does not help infer [tex]\( p \rightarrow r \)[/tex].
Among these conditionals, analyzing [tex]\( r \rightarrow q \)[/tex] (choice 3), let's think step-by-step:
If we have:
- [tex]\( p \rightarrow q \)[/tex] (given)
- [tex]\( r \rightarrow q \)[/tex] (choice 3)
Using contrapositive of [tex]\( r \rightarrow q \)[/tex]:
- [tex]\( \neg q \rightarrow \neg r \)[/tex]
From original [tex]\( p \rightarrow q \)[/tex]:
- Contrapositive of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \neg q \rightarrow \neg p \)[/tex]
If [tex]\( \neg q \rightarrow \neg p \)[/tex] holds true and we assert [tex]\( \neg q \rightarrow \neg r \)[/tex] holds, logically, we can deduce [tex]\( p \rightarrow r \)[/tex].
Therefore, conditional [tex]\( r \rightarrow q \)[/tex] is logically equivalent to helping in constructing [tex]\( p \rightarrow r \)[/tex].
Thus, the correct choice is [tex]\( \boxed{3} \)[/tex]: r \rightarrow q
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.